Modern approaches and some principles of complementary feeding in the first year of life - S.L. Nyankovskyy; О.S. Nyankovska; M.S. Yatsula; O.R. Sadova (Zaslavsky O.Yu., 2021)
Early life feeding habits may potentially alter future metabolism and health in adulthood. The period of the first complementary feeding is the time when children introduce new food different from breast milk and forms a new diet model for their family. This period is important in the transition of the baby from breastfeeding to adult food and is necessary both to provide nutrients for body growth and mental and social development. The timing of supplementation and model of complementary feeding changed over time. Recent literature data show the growing interest and concern of the scientific community about the impact of terms and methods of supplementation on the onset of some diseases, such as iron deficiency anemia, obesity, allergic diseases, celiac disease, diabetes, and others. Nutritional preferences formed in early childhood impact health and eating patterns in adulthood.